2008
DOI: 10.1111/j.1365-2958.2008.06210.x
|View full text |Cite
|
Sign up to set email alerts
|

Control of the cell elongation–division cycle by shuttling of PBP1 protein in Bacillus subtilis

Abstract: SummaryThe characteristic shape of bacterial cells is mainly determined by the cell wall, the synthesis of which is orchestrated by penicillin-binding proteins (PBPs). Rod-shaped bacteria have two distinct modes of cell wall synthesis, involved in cell elongation and cell division, which are believed to employ different sets of PBPs. A long-held question has been how these different modes of growth are co-ordinated in space and time. We have now identified the cell division protein, EzrA, and a newly discovere… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

15
322
1
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 204 publications
(350 citation statements)
references
References 73 publications
15
322
1
5
Order By: Relevance
“…The competition between the various forces at play leading to the ordered distribution of protein complexes in the membrane constitutes in essence an intrinsic amplifier that can act as a sensitive switch enabling the fine-tuning of important cellular processes. Lessfavorable λ values leading to different protein patterns or pattern decay could still be preferentially selected as an expansion of the model; this could occur through the anisotropy introduced by forces generated by molecular structures (e.g., cell curvature) (39) or by the recruitment of specific proteins to subcellular sites, such as the assembly of penicillin binding proteins by MreB or FtsZ (40). Such molecular networks may form a basic system to coordinate life.…”
Section: Resultsmentioning
confidence: 99%
“…The competition between the various forces at play leading to the ordered distribution of protein complexes in the membrane constitutes in essence an intrinsic amplifier that can act as a sensitive switch enabling the fine-tuning of important cellular processes. Lessfavorable λ values leading to different protein patterns or pattern decay could still be preferentially selected as an expansion of the model; this could occur through the anisotropy introduced by forces generated by molecular structures (e.g., cell curvature) (39) or by the recruitment of specific proteins to subcellular sites, such as the assembly of penicillin binding proteins by MreB or FtsZ (40). Such molecular networks may form a basic system to coordinate life.…”
Section: Resultsmentioning
confidence: 99%
“…While it is surprising that a small protein like CrgA interacts with multiple cell division proteins, it is not entirely uncommon. Bacillus subtilis GpsB is also small protein (98 aa) that interacts with MreC, PBP1, and EzrA (9). Deletion analysis showed that the N-terminal 51 residues of CrgA are sufficient for interaction with FtsZ.…”
Section: Discussionmentioning
confidence: 99%
“…Although useful, this two-state model is obviously an oversimplification (35), and recent results reveal that MreB, MreC, MreD, and specific PBPs also form annular rings adjacent to FtsZ rings at the septa of dividing E. coli cells (67). Moreover, some PBPs and division regulators, such as PBP1 and GpsB of B. subtilis, shuttle between the lateral and septal PG synthesis machineries (9).…”
mentioning
confidence: 99%
“…Septal PG synthesis is organized by FtsZ ring formation, followed by the orderly assembly of the divisome complex, which includes a set of PBPs different from those involved in lateral PG synthesis (16,22,23). The mutational interruption of lateral or septal PG synthesis of rod-shaped bacteria generally results in the formation of spherical or elongated cells, respectively (3,4,9,31). Although useful, this two-state model is obviously an oversimplification (35), and recent results reveal that MreB, MreC, MreD, and specific PBPs also form annular rings adjacent to FtsZ rings at the septa of dividing E. coli cells (67).…”
mentioning
confidence: 99%